Analysis of the Relationship between Smoking, Stress, Alcohol, Obesity, Dyslipidemia and Hypertension in the Elderly - Tri Suci; Muhammad Anugerah Ramadhan Hasibuan; Ermi Girsang; Sri Lestari Nasution (Universitas Pahlawan Tuanku Tambusai, 2025)
Hypertension causes the deaths of 8 million people every year, of which 1.5 million deaths occur in Southeast Asia. Overall, the prevalence of hypertension is around 30-45% in adults and the prevalence increases progressively to >60% at ages >60 years. Hypertension is one of the main causes of mortality and morbidity in Indonesia, so it is needed at various levels of health care facilities in an effort to reduce the prevalence and incidence of cardiocerebrovascular disease. The aim of this research is to analyze the relationship between smoking, stress, alcohol, obesity, dysplidemia and hypertension in the elderly at Pustu Desa Deli Tua Dusun IV in 2024. This type of research is analytical quantitative research using a cross sectional approach. The population in this study are elderly people who experience hypertension at Pustu Desa Deli Tua IV in 2024, totaling 95 elderly people. Sampling used total sampling with a total sample of 95 elderly people. The data analysis used in this research is univariate, bivariate and multivariate analysis. The results of the research show that there is a relationship between smoking, stress, obesity and dysplidemia on hypertension in the elderly at the Deli Tua Village Dusun IV Pustu in 2024, but there is no relationship between alcohol and hypertension in the elderly at the Deli Tua Village Dusun IV Pustu in 2024. The variables included The most related to hypertension in the elderly at Pustu Desa Deli Tua Dusun IV in 2024 is the obesity variable (X4). From the results of the research that has been carried out, the suggestions that can be given to elderly hypertensive sufferers are to better maintain their lifestyle by reducing stress, reducing smoking for elderly people who still smoke, maintaining their diet for elderly people who are obese and it is also recommended that they do light exercise with as regular as walking in the morning.